Excessive periostin expression and Th2 response in patients with nasal polyps: association with asthma - Wei, Yi; Ma, Renqiang; Zhang, Jia; Wu, Xingmei; Yu, Guodong; Hu, Xianting; Li, Jian; Liu, Zhuofu; Ji, Wendong; Li, Huabin; Wen, Weiping (Journal of Thoracic Disease, 2018)
Background: Periostin has been shown to be upregulated in chronic rhinosinusitis with nasal polyps (CRSwNP), especially in the CRSwNP patients with asthma. However, the underlying mechanism that how periostin contributes to the polyp genesis remains unclear. Methods: In this study, we collected 63 CRSwNP patients’ nasal polyps (NPs) and 25 control subjects’ uncinated tissues. The expressions of periostin, thymic stromal lymphopoietin (TSLP), and other proinflammatory cytokines were examined using IHC staining, qRT-PCR, Western blot (WB), ELISA and FACS. The eosinophil infiltration, phenotype profiles and clinical characteristics of 2 NP subtypes (eosinophilic and non-eosinophilic) were evaluated. We examined the effects and mechanisms of periostin on human nasal epithelial cells cultured at air-liquid interface (ALI). Results: The expressions of periostin in NPs with asthma were higher than without asthma and the control nasal mucosa and positively associated with the TSLP (P